2016
DOI: 10.1038/bjc.2016.44
|View full text |Cite
|
Sign up to set email alerts
|

BRAF-V600E expression in primary nodular melanoma is associated with aggressive tumour features and reduced survival

Abstract: Background:Around 50% of primary melanomas harbour BRAF mutations, but their prognostic impact has not been clear. Recently, a BRAF-V600E mutation-specific antibody has become available for immunohistochemistry. Here, we investigated for the first time the prognostic impact of BRAF-V600E protein expression in primary melanoma.Methods:In a patient series of 248 nodular melanomas, BRAF-V600E and total BRAF expression were assessed by immunohistochemistry using tissue microarray sections of paraffin-embedded arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 46 publications
7
65
1
Order By: Relevance
“…Most of these studies concluded that BRAF mutation was in association with younger age at diagnosis (Heppt et al, ; Hugdahl et al, ; Meckbach et al, ), truncal lesion (Heppt et al, ; Hugdahl et al, ), and the superficially spreading melanoma histotype (Heppt et al, ; Meckbach et al, ), we agree with these findings. Regarding major prognostic indicators, precious studies demonstrated BRAF‐mutant melanomas were correlated with increased tumor thickness (Ellerhorst et al, ; Hugdahl et al, ), higher mitotic count (Ellerhorst et al, ; Hugdahl et al, ; Long et al, ; Meckbach et al, ) and presence of ulceration (Akslen et al, ; Ellerhorst et al, ; Hugdahl et al, ). Conversely, we found no similar associations in our patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Most of these studies concluded that BRAF mutation was in association with younger age at diagnosis (Heppt et al, ; Hugdahl et al, ; Meckbach et al, ), truncal lesion (Heppt et al, ; Hugdahl et al, ), and the superficially spreading melanoma histotype (Heppt et al, ; Meckbach et al, ), we agree with these findings. Regarding major prognostic indicators, precious studies demonstrated BRAF‐mutant melanomas were correlated with increased tumor thickness (Ellerhorst et al, ; Hugdahl et al, ), higher mitotic count (Ellerhorst et al, ; Hugdahl et al, ; Long et al, ; Meckbach et al, ) and presence of ulceration (Akslen et al, ; Ellerhorst et al, ; Hugdahl et al, ). Conversely, we found no similar associations in our patients.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have investigated the association between BRAF mutation and clinicopathological features in melanoma (Akslen et al, ; Ellerhorst et al, ; Heppt et al, ; Hugdahl et al, ; Inumaru et al, ; Maldonado et al, ; Mann et al, ; Meckbach et al, ; Moreau et al, ; Picard et al, ; Shinozaki et al, ). Most of these studies concluded that BRAF mutation was in association with younger age at diagnosis (Heppt et al, ; Hugdahl et al, ; Meckbach et al, ), truncal lesion (Heppt et al, ; Hugdahl et al, ), and the superficially spreading melanoma histotype (Heppt et al, ; Meckbach et al, ), we agree with these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, a study by Hughahl et al (22) revealed the association between higher rates of BRAF V600 immunohistochemistry expression and increased tumour thickness, presence of ulceration and higher rates of mitosis. Conversely, several papers have declared that the BRAF V600 mutation has no impact on clinicopathological features or survival (22)(23)(24)(25)(26). Although there was no significant correlation in the present study, the patients with the BRAF V600 mutation were younger than the patients with wild-type BRAF, and NM was detected more commonly in BRAF V600-mutated patients.…”
Section: Discussionmentioning
confidence: 98%